2008
DOI: 10.1158/1078-0432.ccr-08-1329
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence, Correlation with Tumor-Infiltrating Inflammation, and Prognosis of Phosphorylated STAT3 Expression in Human Gliomas

Abstract: Purpose: The signal transducer and activator of transcription 3 (STAT3) is frequently overexpressed in most cancers, propagates tumorigenesis, and is a key regulator of immune suppression in cancer patients. We sought to determine the incidence of phosphorylated STAT3 (p-STAT3) expression in malignant gliomas of different pathologic types, whether p-STAT3 expression is a negative prognostic factor, and whether p-STAT3 expression influences the inflammatory response within gliomas. Methods: Using immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(145 citation statements)
references
References 55 publications
8
135
0
2
Order By: Relevance
“…Moreover, immunohistochemical expression of p-STAT3 in nasal NKTCL tissues was found to be positively correlated with the Ki-67 levels in these cases with Fisher's exact test analysis. This was in accordance with previous studies of glioma and colorectal cancers in which STAT3 activation was generally correlated with poor prognosis (23,24). Based on the published data, STAT3 has gained notoriety as a hub to relay multiple oncogenic signals modulating transcription of target genes.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, immunohistochemical expression of p-STAT3 in nasal NKTCL tissues was found to be positively correlated with the Ki-67 levels in these cases with Fisher's exact test analysis. This was in accordance with previous studies of glioma and colorectal cancers in which STAT3 activation was generally correlated with poor prognosis (23,24). Based on the published data, STAT3 has gained notoriety as a hub to relay multiple oncogenic signals modulating transcription of target genes.…”
Section: Discussionsupporting
confidence: 91%
“…It has been also shown that pSTAT3-Y705 activation in tumor cells participates in locally blocking immune cell maturation and activation by modifying tumor secretome (48). Moreover, pSTAT3-Y705 expression in glioma tumors has been positively correlated to tumor grade as well as to a worse patient prognosis (1,37). Those findings suggested that STAT3 activation is involved in glioma tumorigenesis and tumor aggressiveness.…”
Section: Concordant Studies Have Reported Signal Transducer and Activmentioning
confidence: 99%
“…In particular, STAT3 is a key candidate causing the malignant progression of glioma, and its aberrant activation has been a poor prognostic factor for survival in glioma patients (5)(6)(7)(8)(9). Phosphorylated STAT3 (p-STAT3) leads to transcriptional activation of downstream genes involved in processes such as cell proliferation, differentiation, cell survival, angiogenesis, and cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%